Analysis of Motor Complication and Relative Factors in a Cohort of Chinese Patients with Parkinson’s Disease - Baihua Sun; Tao Wang; Nianying Li; Jin Qiao (Parkinson's Disease)
Objective. Motor complications are common in Parkinson’s disease (PD). The reported occurrence of motor complications varies across regions and races. The aim of our study was to describe the development of dyskinesias and motor fluctuations among Chinese PD patients and the relative risk factors. Methods. In the current cross-sectional survey study, PD patients with motor fluctuations and dyskinesia were enrolled from March to November 2018 in Shaanxi province, a northwest area of China. Data were collected by the movement disorder specialists. A self-designed questionnaire was utilized during face-to-face interviews. In addition, the relevant factors of motor complications were analyzed by univariable and multivariable analyses. Results. Of the166 PD patients recruited, 52 (31.33%) and 25 (15.06%) patients had motor fluctuations and dyskinesia, respectively, which occurred in 6.76 ± 3.77 and 8.61 ± 4.46 years after the onset of motor symptoms and 5.37 ± 3.33 and 6.80 ± 3.43 years after the treatment of levodopa therapy, respectively. Patients with motor fluctuations and dyskinesias had longer disease duration, younger onset age, higher Hoehn–Yahr stages and UPDRS III scores, higher daily levodopa dosage and levodopa equivalent daily dose (LEDD), and longer duration of levodopa treatment (P<0.05). Bradykinesia-rigidity dominant patients had higher incidences of motor fluctuations (61.54% vs 38.46%) and dyskinesias (68.00% vs 32.00%) than tremor-dominant patients (P<0.05). Results of the multivariate logistic regression analyses showed that the duration of levodopa therapy, age of the onset, and bradykinesia-rigidity dominant type were independent risk factors of motor fluctuations (P<0.05). In addition, duration of disease and bradykinesia-rigidity dominant type were independent risk factors of dyskinesia (P<0.05). Conclusions. The rate of motor fluctuations was higher than dyskinesias in Chinese patients with Parkinson’s disease. Patients with younger age onset, bradykinesia-rigidity dominant type, longer disease duration, and longer duration of levodopa therapy are more likely to develop motor complications.